Porphyromonas gingivalis prevalence and gyrA gene detection linked to mercury exposure in periodontitis among gold miners - HELENA JELITA; HARUN ACHMAD; SYAMSUL ARIFIN; DAHLIA HERAWATI; IRENE EDITH RIEUWPASSA; RASMIDAR SAMAD; ANDI ROFIAN SULTAN; HANASIA HANASIA; FIRDAUS HAMID (Society for Indonesian Biodiversity, 2026)
Abstract. Jelita H, Achmad H, Arifin S, Herawati D, Rieuwpassa IE, Samad R, Sultan AR, Hanasia, Hamid F. 2026. Porphyromonas gingivalis prevalence and gyrA gene detection linked to mercury exposure in periodontitis among gold miners. Biodiversitas 27 (4): d270437. https://doi.org/10.13057/biodiv/d270437. The oral cavity is a dynamic ecosystem hosting diverse anaerobic microorganisms that influence oral health. Porphyromonas gingivalis, a key Gram-negative anaerobe, is strongly implicated in periodontitis pathogenesis. Chronic mercury (Hg) exposure, particularly among artisanal gold miners, has been associated with microbial dysbiosis and antibiotic resistance genes. This study investigated the relationship between salivary Hg levels, subgingival anaerobic bacteria, detection of P. gingivalis and gyrA in periodontitis among gold miners. A cross-sectional design included 60 participants (30 gold miners and 30 non-gold miners). Subgingival plaque was cultured anaerobically and identified using Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS); Polymerase Chain Reaction (PCR) detected P. gingivalis and gyrA. Salivary Hg concentrations were determined using Atomic Absorption Spectrophotometry with a Mercury Vapor Unit (AAS-MVU). Median salivary Hg levels were significantly higher in miners than non-miners (0.09 µg/L [0.03-0.22] vs. 0.03 µg/L [0.03-0.03]; p<0.001), although all values remained below the 5 µg/L salivary threshold. Culture recovery was low, identifying Prevotella denticola and P. melaninogenica among miners and Bifidobacterium sp. among non-miners. PCR detected P. gingivalis in 80.00% of miners and 63.33% of non-miners (p = 0.152). In contrast, gyrA detection was higher in miners (19/30, 63.33%) than in non-miners (10/30, 33.33%, p = 0.020). Mann–Whitney analysis showed no significant differences between salivary Hg and detection of P. gingivalis (p = 0.420) or gyrA (p = 0.953). However, a significant association between P. gingivalis and gyrA was observed using the Chi-square test (χ² = 22.191, p<0.001; φ = 0.61). Although P. gingivalis prevalence did not differ significantly, chronic low-dose Hg exposure was associated with higher gyrA detection and distinct anaerobic bacteria in miners, suggesting Hg may be associated with resistance-related microbial dynamics in periodontal biofilms. Larger studies using quantitative PCR and metagenomic approaches are needed to clarify underlying mechanisms.